PENGARUH UKURAN PERUSAHAAN, RISIKO BISNIS DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PERUSAHAAN MANUFAKTUR - Rupianti, Yayuk (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to prove the influence of the company size, the business risk, and theprofitability on the capital structure which go in the companys manufacturing of the basic industryand chemical sector which is listed in the Indonesia Stock Exchange (IDX). This research usessecondary data which was in the form of financial report for the period of December 31st 2011, which islisted on the Indonesia Stock Exchange (IDX). As many as 60 companies are used as sample in thisresearch. Classic assumption test, multiple linear regression analysis, t-test, F-test, and thedetermination coefficient of the size of the company, business risk, and profitability, as the independentvariable are used as the data analysis. (1) the company size variable partially has no significant effectto the capital structure; (2) Risk Business variable partially gives negative effect and significantlyinfluence to the capital structure; (3) profitability variable partially gives positive effect andsignificantly influence to the capital structure.Keywords: Capital Structure, Company Size, Business Risk, Profitability